2012
DOI: 10.1007/s10549-012-2370-4
|View full text |Cite
|
Sign up to set email alerts
|

Interpersonal influences and attitudes about adjuvant therapy treatment decisions among non-metastatic breast cancer patients: an examination of differences by age and race/ethnicity in the BQUAL study

Abstract: Patients are increasingly involved in cancer treatment decisions and yet little research has explored factors that may affect patient attitudes and beliefs about their therapeutic choices. This paper examines psychosocial factors (e.g., attitudes, social support), provider-related factors (e.g., communication, trust), and treatment considerations in a prospective study of a sample of early stage breast cancer patients eligible for chemotherapy and/or hormonal therapy (BQUAL cohort). The data comes from a multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 74 publications
1
26
1
Order By: Relevance
“…Results from the study shows that older breast cancer patients made treatment decisions on their own. This finding is inconsistent with a previous study who found that older breast cancer patients were more comfortable to leave the treatment decisions to the physician or assume a less active role in making treatment decisions (Pinquart and Duberstein, 2004;Gaston and Mitchell, 2005;Almyroudi et al, 2010;Shelton et al, 2012).…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…Results from the study shows that older breast cancer patients made treatment decisions on their own. This finding is inconsistent with a previous study who found that older breast cancer patients were more comfortable to leave the treatment decisions to the physician or assume a less active role in making treatment decisions (Pinquart and Duberstein, 2004;Gaston and Mitchell, 2005;Almyroudi et al, 2010;Shelton et al, 2012).…”
Section: Discussioncontrasting
confidence: 98%
“…The reasons were that (1) patients did not know enough about breast cancer, (2) they believe that doctors were the experts, (3) they felt unqualified to make judgments about medical problems, and (4) patients may have difficulty in understanding physicians' terminology (Maly, 2004). Besides health professionals, family members also play an important role in assisting cancer patients make decisions on treatment, especially patients 65 years and older (Shelton et al, 2012). A review of literature on decision-making and information provision in patients with advanced cancer pointed out that those who took an active role were younger and had a higher education level (Gaston and Mitchell, 2005).…”
Section: Older Women Breast Cancer Survivors: Decision Making Sourcementioning
confidence: 99%
“…This finding supports emerging evidence that a combination of both clinical and nonclinical factors play an important role throughout the continuum of BC care delivered to AA women. 40 Our study has several limitations. The participation rate for older women was poorer than in younger women.…”
Section: Discussionmentioning
confidence: 91%
“…These 5 studies included publicly insured patients who were enrolled in state Medicaid programs 19,60,81,87 or Medicare’s low-income subsidy program. 22 Of all included articles, 6 77,78,80,81,83,86 examined primary data collected through the use of surveys, interviews, or focus groups; of these, 3 77,80,83 included self-reported barriers to care (Table 2). Eight studies 19,22,60,79,82,83,85,87 used large secondary data sources or medical records to examine racial/ethnic and socioeconomic disparities in ET use; of these, 3 77,79,86 examined adjuvant breast cancer therapy broadly, including not only ET use but also either chemotherapy, or chemotherapy with radiation therapy.…”
Section: Resultsmentioning
confidence: 99%
“…22 Of all included articles, 6 77,78,80,81,83,86 examined primary data collected through the use of surveys, interviews, or focus groups; of these, 3 77,80,83 included self-reported barriers to care (Table 2). Eight studies 19,22,60,79,82,83,85,87 used large secondary data sources or medical records to examine racial/ethnic and socioeconomic disparities in ET use; of these, 3 77,79,86 examined adjuvant breast cancer therapy broadly, including not only ET use but also either chemotherapy, or chemotherapy with radiation therapy. Although these studies evaluated chemotherapy and radiation therapy as dependent variables, some studies included these treatment variables (i.e., surgery, chemotherapy, radiation) as predictor variables of ET use 19,22,60,81,82,84,87 and other studies 78,80,83 , did not include treatment variables in their analyses.…”
Section: Resultsmentioning
confidence: 99%